“I don’t know if it is fake or real news” how little Indonesian university students understand social media literacy - M. Syam, Hamdani; Nurrahmi, Febri (Penerbit Universiti Kebangsaan Malaysia, 2020)
Concerns over fake news have been raised in Indonesia since there has been a significant increase in the spreading of fake news via social media. University students, as the most active social media users, are susceptible to consume and distribute fake news. This study is motivated by the assumption that media literacy interventions help users resist fake news. However, limited studies have specifically addressed their level of media literacy in identifying fake news. Using the new media literacy framework, this study analysed the level of media literacy to process fake news on social media among university students in Aceh. A total of 500 undergraduate students from Syiah Kuala University and Ar-Raniry State Islamic University participated in the survey. Following the survey, 28 students were selected to take part in four focus group discussions. The findings showed that students' degree of media literacy concerning fake news is relatively low. Although almost all students demonstrated a good skill in using multiple social media platforms and understanding information they received, they were not confident in their abilities to distinguish between fake and real news. Surprisingly, some students deliberately share controversial posts on social media for no reason or to please themselves. The study suggests that program of media literacy should emphasise the identification of fake news and the consequences of its distribution.